Modulation of cigarette smoke induced alterations by aqueous Ocimum sanctum leaf extract in pulmonary tissue of rodents - Pavitra Ranawat; Navdeep Kaur; Ashwani Koul (Scientific Reports, 2023)
Abstract Smoking has been associated with an increased risk of asthma, lung cancer, cardiovascular diseases, chronic bronchitis, and a massive amount of oxidative stress. The present study was undertaken to determine the modulatory effects of Holi Basil/Tulsi, (Ocimum sanctum) leaf extract on cigarette smoke-induced pulmonary damage in mice. Cigarette smoke (CS) inhalation increased the levels of pulmonary lipid peroxidation, and reactive oxygen species and decreased the levels of glutathione. Histoarchitectural alterations and enhanced tissue lactate dehydrogenase (LDH) activity in pulmonary tissue was distinctly indicative of damage. Enhanced mucin production was also observed through mucicarmine and Alcian Blue-Periodic Acid Schiff (PAS) staining. Increased expression of MUC5AC was also observed. Alterations in the lung were also evident through FTIR studies. Administration of Ocimum sanctum leaf extract (80 mg/kg b.w) to CS exposed mice ameliorated these alterations to a greater extent. These findings are suggestive of the fact that Ocimum sanctum leaf extract effectively modulated CS-induced deleterious effects on pulmonary tissue.